PERBANDINGAN KADAR GLUKOSA SERUM DARI DARAH YANG LANGSUNG DISENTRIFUGE DAN DITUNGGU BEKU SEBELUM DISENTRIFUGE METODE GOD-PAP TAHUN 2021 - Ed, Erwin; Halius, Nadiya Lutfiah; Mutholib, Abdul; Asrori, Asrori; Hermansyah, Herry; Handayani, Handayani; Dani, Hamril; Afriayani, Iis; Febriyani, Erisa (Journal of Medical Laboratory and Science, 2022)
Background : Glucose examination, can use whole blood, serum, and urine samples. Serum was obtained from blood which was awaited to freezing first and then centrifuged at 3000 rpm for 15 minutes. However, the reality in the employment to shorten the time, blood is often centrifuged immediatelly without waiting for the blood to freezing. Purpose : To determine whether there is differences in serum glucose levels from the blood that is immediately centrifuged and waited for freezing before centrifuge. Methods :This research is an analytical research using cross sectional approach. The research sample was taken from 30 students of Medical Laboratory Technology, Poltekkes Palembang. Result :The data obtained were analyzed statistically by using the test t dependet we got the average serum glucose level from blood that is immediately centrifuge was 83,80 mg/dL. The average serum glucose from blood waited for freezing before centrifuge was 76,50 mg/dL. Obtained result P value = 0,000012 means p<0,05. Conclusion : There is statistically meaningful differences beetwen serum glucose levels from the blood that is immediately centrifuge and waited for freezing before centrifuge. Suggestion :it is recommended for laboratory technology should be examined against blood that has waited for freezing before centrifuge, because blood that is immediately centrifuge can increase glucose levels so that the result examination increase falsely.